BENEFICIAL EFFECTS OF ALLIUM SATIVUM LINN IN EXPERIMENTAL CHOLESTEROL ATHEROSCLEROSIS IN CHICKEN Part - 1. Protective Effects - KHALID, QAMAR; SULTANA, LIAQUAT; SARWAR , MOHAMMAD; AHMAD, YUSUF (Biological Sciences - PJSIR, 2022)
Beneficial effects ofgarlic have beenestablished in a chicken modelby biochemical aswell as anatomical evidence. Garlic wa fed to chickens simultaneously with cholesterol to investigate its protective effects on induction of experimental atherosclerosis. The results have shown thalgarlic administration leads to a significant decrease in the level of triglyccrides, total cholesterol and LDL (+VLDL)-cholestcrol in the plasma of chickens fed on cholesterol-enriched feed. These biochemical findings correlate well with the assessment of aortic damage observed in these animals after sacri fice at the end of 12 weeks' study period. The damage being significantly lower as compared to that found in the animals not given garlic. Possible mechanisms by which garlic could exerts its beneficial effects arc discussed.